‘High schools High on life’: Development of an Intervention to Reduce Excessive Drinking in Danish High Schools - Pisinger, Veronica Sofie Clara; Hoffmann, Sofie Have; Pålsson, Lotte; Dalum, Peter; Grønbæk, Morten Klöcker; Tolstrup, Janne Schurmann; Thygesen, Lau Caspar; Krølner, Rikke Fredenslund (Frontiers in Public Health, 2020)
Background: Clear documentation of the understanding of the problem, process of development, and content of interventions is essential to enable other researchers to understand why interventions succeed or fail and to enable researcher to build on previous evidence and replicate and adapt findings in other contexts. In this paper we describe the rationale, intervention development, and final design of the ‘High schools High on life' intervention; a high school-based, multi-component intervention to reduce excessive drinking among Danish high school students. Methods: The development of the intervention ‘High schools High on life´ was guided by the planning steps of the Intervention Mapping protocol (IM) in combination with the behavior change wheel and the behavior change techniques, theory, evidence, practice and new empirical studies of contextual factors in the Danish high school setting. Results: The development process resulted in a multi-component intervention with the following intervention elements: a school environmental component targeting school alcohol policies and norms, a school educational component addressing students’ social norms around alcohol, and a parental component encouraging parent-child communication around alcohol. Discussion: Not all steps of IM were followed rigidly. However, IM proved useful as a planning tool in combination with the behavior change wheel and the behavior change techniques, as it provided a systematic approach to the intervention development process. IM forced the research group to be explicit about decisions and choices throughout the planning process. The transparency of the developmental process and theoretical, empirical and practical/contextual foundation of the ‘High schools High on life’ intervention may enable future intervention studies to build on our findings and accumulate knowledge to reduce excessive drinking among young people.